Organizational citizenship behaviors in the portuguese hospitality industry: a study on sociodemographic and professional variables - Cordeiro, João Pedro Pina (2024)
The aim of this research is to reflexively analyze and discuss organizational citizenship behaviors. By conducting an empirical test based on the assertions within the fields of the positive organizational behavior and the social identity theory, the specific objective is to analyze the relation- ship between organizational citizenship and sociodemographic and professional variables. A study was carried out by surveying employees of Portuguese hotel units. The sample consisted of 798 em- ployees, mostly males, between 30 and 34 years old, with secondary school education, serving as operatives or undifferentiated employees, and having middle levels of seniority in the organization. The main results show that hotel employees develop organizational citizenship behaviors, albeit of different types and levels, which are supported by some sociodemographic and professional variables. The findings show that age and seniority are the most important and strongest variables significantly related to organizational citizenship behaviors. This study has several implications, highlighting the role and support that managers and decision-makers must have in reinforcing positive volun- tary personal and social behaviors among hotel employees. This research aims to contribute to the formulation and implementation of management strategies anchored in organizational citizenship behaviors, supporting the formulation of management systems centered on behavioral attitudes at work in the context of the hotel sector.